Is the shrimp Macrobrachium amazonicum sold in an urban center in the central Brazilian Amazon contaminated with microplastics? - GUIMARÃES, Gabriel dos Anjos; MORAES, Beatriz Rocha de; ANDO, Rômulo Augusto; PEROTTI, Gustavo Frigi; SANT’ANNA, Bruno Sampaio; HATTORI, Gustavo Yomar (Acta amazonica, 2024)
ABSTRACT Growing global concern surrounds microplastics, found in various environments. However, data on microplastics contamination in salted shrimp and associated health risks remain scarce. We analyzed whether salted shrimps sold in markets in a main city in Amazonas state (Brazil), are contaminated with microplastics. We examined 150 specimens of Macrobrachium amazonicum and found 396 potential microplastics in 129 individuals (86%). The number of particles per gram of body mass was highest in the gastrointestinal tract, with 60% of them ranging in size from 1,000 to 5,000 µm, predominantly dark blue fibers (80%). The contamination likely originates from the environment and the salt used during processing in the region where the shrimps are captured. Our findings point to a potential health risk to the many consumers of salted shrimp in the Amazon region. RESUMO Há uma crescente preocupação global com os microplásticos, encontrados em diversos ambientes. No entanto, ainda faltam dados sobre a contaminação por microplásticos em camarão salgado e os riscos à saúde associados. Analisamos se os camarões salgados vendidos em mercados de uma cidade principal no estado do Amazonas (Brasil) estão contaminados com microplásticos. Examinamos 150 espécimes de Macrobrachium amazonicum e encontramos 396 potenciais microplásticos em 129 indivíduos (86%). O número de partículas por grama de massa corporal foi mais alto no trato gastrointestinal, com 60% delas variando em tamanho de 1.000 a 5.000 µm, predominantemente fibras de cor azul escura (80%). A contaminação provavelmente se origina do ambiente e do sal utilizado durante o processamento na região onde os camarões são capturados. Nossos resultados indicam um potencial risco à saúde para os muitos consumidores de camarões salgados na região amazônica.